The Chromosome-Scale Assembly of the Curcuma alismatifolia Genome Provides Insight Into Anthocyanin and Terpenoid Biosynthesis - Dong, Qing; Zou, Qing-Cheng; Mao, Li-Hui; Tian, Dan-Qing; Hu, Wei; Cao, Xue-Rui; Ding, Hua-Qiao (Frontiers in Plant Science, 2022)
Curcuma alismatifolia, a bulbous flower known for its showy bracts, is widely used around the world as a cut flower, potted, and garden plant. Besides its ornamental value, this species is rich in terpenoid metabolites and could serve as a resource for essential oils. Here, we report a chromosome-level genome assembly of C. alismatifolia and describe its biosynthetic pathways for anthocyanins and terpenoids. This high-quality, assembled genome size is 991.3 Mb with a scaffold N50 value of 56.7 Mb. Evolutionary analysis of the genome suggests that C. alismatifolia diverged from Zingiber officinale about 9.7 million years ago, after it underwent a whole-genome duplication. Transcriptome analysis was performed on bracts at five developmental stages. Nine highly expressed genes were identified, encoding for six enzymes downstream of the anthocyanin biosynthetic pathway. Of these, one gene encoding F3′5′H might be a key node in the regulation of bract color formation. Co-expression network analysis showed that MYB, bHLH, NAC, and ERF transcription factors collectively regulated color formation in the bracts. Characterization of terpenoid biosynthesis genes revealed their dispersal and tandem duplications, both of which contributed greatly to the increase in the number of terpene synthase genes in C. alismatifolia, especially to species-specific expansion of sesquiterpene synthase genes. This work facilitates understanding of genetic basis of anthocyanin and terpenoid biosynthesis and could accelerate the selective breeding of C. alismatifolia varieties with higher ornamental and medicinal value.